Taur-Taur of the Simalungun Batak Ethnic Group: A Pragmatic Study - Puji Syukur Giawa; Warisman Sinaga; Tomson Sibarani (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study discusses the Taur-taur of the Batak Simalungun ethnic group from a pragmatic perspective as part of an oral cultural expression rich in meaning. Taur-taur is a chant-like or humming speech act that serves to convey emotional feelings, such as sadness, longing, and hope, which are greatly influenced by the social context and the situation in which it is presented. This study aims to identify the form of speech and analyze the types, functions, and meanings of speech acts contained in Taur-taur. The method used is descriptive qualitative with data collection techniques through in-depth interviews and recordings of Taur-taur performances. The data obtained were then transcribed, reduced, and classified based on John Searle's speech act theory. The results of the analysis show that the most dominant types of assertive speech acts include suggesting (1), telling (2), explaining (9), stating (35), and blessing (2). Directive types include inviting (1), requesting (3), ordering (9), begging (1), and asking (2). Expressive speech acts are found in the form of condolences (3) and complaining (6), while commissives only appear in the form of promising (1). The dominance of assertive speech acts indicates that Taur-taur speakers tend to convey information, experiences, and feelings directly and reflectively. This finding confirms that Taur-taur functions not only as an aesthetic expression but also as a medium of cultural communication that represents values, emotions, and social relationships in Simalungun society.